Pengaruh Media Pembelajaran LCD Terhadap Minat Belajar Siswa Pada Pembelajaran IPS Di SDN 15 Tilamuta Kabupaten Boalemo - Mohamad Akuba; Winda Anggriyani Uno (Universitas Syiah Kuala, 2023)
The research aims to determine the influence of instructional media on students' interest in social studies learning at SDN 15 Tilamuta, Boalemo Regency. This study adopts a quantitative research method that aims to test research hypotheses related to the variables under investigation. It is a study that tests theories by measuring research variables using numerical data and conducting data analysis through statistical procedures. The study utilizes the ex post facto methodFrom the analysis results, it is revealed that the influence of LCD instructional media (X) on students' interest in learning at SDN 15 Tilamuta is 0.374, which significantly affects students' interest in learning at SDN 15 Tilamuta. The regression coefficient indicates that the influence of LCD instructional media on interest in learning aligns with the theory. Furthermore, based on the t-test value, the Tukey value obtained is 3.653, and the significance value of the LCD instructional media is 0.001, which is smaller than the probability value of 0.05. This is acceptable because the LCD instructional media (X) is not the sole